The influence of sodium selenite and 6-benzylaminopurine on the production process of red currant - P. S. Prudnikov; O. D. Golyayeva (Овощи России)
Relevance. In modern climatic conditions, the suppression of production process occurs against the background of short-term or long-term exposure to unfavorable environmental factors on agricultural plants, and, therefore, yield decreases. In this regard, there is a need for the use of growth regulators with protective and stimulating effects on many physiological processes.The aim of the work was to study the influence of the element selenium and 6-benzylaminopurine on the production process of red currant.Methods. Foliar treatments with solutions of sodium selenite and 6-benzylaminopurine (6-BAP) were made after flowering plants of the Dana and Asya varieties of the VNIISPK. The currant leaves were taken from annual shoots for determine the content of abscisic acid (ABA), the amount of pigments, and the rate of light reactions of photosynthesis. The parameters of the fruit brush of plants were recorded.Results. It was shown that treatments with sodium selenite and 6-benzylaminopurine contribute to a decrease of 2.1-3.5 times in the leave tissues of the endogenous ABA level, increase the chlorophyll biosynthesis by 27.5-48.0% and accelerate by 19.3-45.8% electron transfer rate on the level of light photosynthesis reactions. Treatment with selenium and 6-BAP of Dana plants increased the average mass of the fruit brush by 19.30% and 24.5%, respectively, Asya varieties by 20.7 and 35.8%. The increase in the average mass of the fruit brush occurred due to the enlargement of the average mass of one berry in it. It was shown that selenium and 6-BAP in the Dana variety increased the weight of the berry by 27.3% and 47.3%, in Asya by 33.3% and 45.8%. The treatment did not have a significant effect on the amount of sugars. Thus, for increase the production process, it is advisable to make foliar treatments with sodium selenite and 6-BAP during the growing season on red currant plants.